BIMBINGAN PRAKTIKUM KIMIA UJI INDIKATOR ALAMI DI SMA NEGERI 1 SINGOSARI - Fitriana, Nurin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2020)
Abstract: Practicum activities in learning Natural Sciences in the school environment is one of the effective methods to achieve learning objectives. Because in learning activities there are many concepts that can be explained if students carry out scientific activities or with laboratory tests. Singosari 1 High School is one of the high schools located on Jl. Ki Hajar Dewantara Singosari, Malang Regency. This community service activity aims to provide practical guidance to students in SMA Negeri 1 Singosari for Chemistry subjects. This is based on the results of interviews with chemistry teachers who showed that many students had difficulty in acid-base material. The method used needs analysis and is measured with quantitative data in the form of a tabulated questionnaire. The results of this service can be measured qualitatively and quantitatively, namely a questionnaire given to students that shows that there is a positive response and most feel very satisfied with the practicum activities undertaken. Students feel they can construct their understanding independently. Keywords: Practicum, acid-base, IPA